Hacia Una Caracterización De La Producción Oral Espontánea De Los Estudiantes Universitarios Benineses De ELE - Sossouvi, Laurent-Fidèle (European Scientific Journal, ESJ, 2016)
This exploratory study analyzed the errors made by Beninese university students of Spanish as a Foreign Language (n = 100) in situations of spontaneous speech both inside and outside the classroom, in order to characterize them linguistically. The corpus contains 10 hours of high quality recorded spontaneous conversations or interactive communicative activities. The results indicate the main categories of interference of the available languages, heterogeneous sources of errors, highlighting the creativity and the dynamism of the participants’ linguistic practices, showing a tendency to mix or switch the codes of their repertoire. Finally, possible pedagogical and curricular suggestions are explored.